Unintentional formation of mixed chloro-bromo diphenyl ethers (PBCDEs), dibenzo-p-dioxins and dibenzofurans (PBCDD/Fs) from pyrolysis of polybrominated diphenyl ethers (PBDEs). (December 2022) - Liang, Jiahao; Wang, Rui; Liu, He; Xie, Danping; Tao, Xueqin; Zhou, Jiangmin; Yin, Hua; Dang, Zhi; Lu, Guining
Abstract: This study presents the comprehensive investigation for formation pathways of chloro-bromo-mixed products from the pyrolysis of polybrominated diphenyl ethers (PBDEs). In the study, a total of 23 PBDEs with bromination levels from mono-to deca-were selected. Each PBDE standard was sealed in the glass vial and then heated under 450 °C in the muffle furnace to simulate the pyrolysis process. The results demonstrated that PBDEs in the glass vials can unintentionally transform into chloro-bromo diphenyl ethers (PBCDEs) and dibenzo-p-dioxin and dibenzofurans (PBCDD/Fs) during the pyrolysis process. Atmosphere pressure gas chromatography (APGC) coupled with high-resolution mass spectrometry (HRMS) was used to identify these pyrolysis products, which demonstrated that all investigated nPBDEs (n represents the number of bromine substituents) can unintentionally transform into Cl1 -(n-1)BDEs, Cl2 -(n-2)BDEs, Cl1 -(n-1)BDFs, and Cl1 -(n-3)BDDs, while some nPBDEs can transform into Cl1 -(n-2)PBDD/Fs during pyrolysis. Experimental phenomena assisted with density functional theory (DFT) calculations reveal that Cl atom can substitute at C–Br rather than C–H, and Cl1 -(n-1)BDEs can be easily generated by Cl atom attacking at C–Br sites with low energy barriers (3.66–11.9 kcal/mol). In addition, nPBDEs with lower bromination levels are more favorable to generate Cl1 -(n-1)BDEs than those with higher bromination levels. Further DFT calculations suggest that PBDEs are preferentially first transformed into Cl1 -(n-1)BDEs, then subsequentially transform into PBCDD/Fs. We believe the results of this study can greatly improve our understanding of the transformation mechanism from PBDEs to cholo-bromo-mixed products in thermal treatment processes and provide new insight into controlling the emission of toxic cholo-bromo-mixed products. Graphical abstract: Image 1 Highlights: Unintentional negligible Cl can significantly affect the PBDEs pyrolysis products. PBCDD/Fs and PBCDEs are qualified during pyrolysis of authentic PBDE standards. Lower brominated PBDEs are more preferential to generate PBCDEs than highly ones. PBDEs .→ PBCDEs → PBCDD/Fs is the most plausible pathway for formation of PBCDD/Fs.